(untitled) (Bangladesh Journal of Neuroscience, 2009)
Thirty five patients were selected to evaluate the outcome & prognosis of metastatic brain tumour in the department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University, (BSMMU) Dhaka from February 2002 to December 2005. A structured questionnaire was made. Data were collected after the patient admission. All patients were evaluated with detailed history and clinical examination. MRI of Brain of these patients revealed intracranial lesions highly suspicious of metastatic brain tumour. Investigations like USG of the whole abdomen and x-ray chest were done to locate any primary site. Some of the primary lesions were confirmed by FNAC and histological examinations. Solitary intracranial space occupaing lesion (ICSOL) and sizable lesion among the multiple lesions were treated by surgery, and then histopathological examination were done followed by radiotherapy and / or chemotherapy. This was a prospective study. This study showed the highest age of incidence of tumours were above 60 years. Male predominated than female (60.00%). Among the clinical features the most common sign was hemiparesis (34.28%). The commonest site of lesion was in frontal region (34.28%). Histopathological reports showed adenocarcinoma 40.00%, small cell carcinoma of lungs 28.57%, squamous cell carcinoma 22.85%, follicular carcinoma of thyroid 5.71%. Treatment options were surgery, radiotherapy and chemotherapy. Sixty percent patients were improved after treatment. Highest survival rate was 3 to 6 months with treatment (31.42%). This study revealed that commonest type of brain metastases was adenocarcinoma and primary site of lesion was lungs. Best option of treatment was surgery plus radiotherapy and longest survival rate of 1 year was in 20.00% cases. DOI: http://dx.doi.org/10.3329/bjn.v24i1.3036 Bangladesh Journal of Neuroscience 2008; Vol. 24 (1) : 17-23